Development of the Teaching About Material Responsibilities in Labor Law: Array - Stahi, Tatiana; Robea, Mariana (Journal of Danubian Studies and Research, 2020)
One of the problems of modern civil and labor law is the ratio of the institutions of material and property responsibility, in particular, the application of the provisions of responsibility in relations involving the possibility of joint use of civil and labor law. For example, in the event of harm to the interests of third parties by an employee in the performance of his job duties. For the correct and reasonable application of the norms of liability, it is necessary to determine the role and place of property and labor liability in the system of legal liability as a whole. The article examines the development of the doctrine of material and property responsibility in labor law. Fulfillment of the obligations of the employee and the employer in accordance with labor law. A necessary element is damage to property or health of the employer, employee, respectively.